Fast Versus Slow Recruitment Maneuver at Different Degrees of Acute Lung Inflammation Induced by Experimental Sepsis. (April 2016) - Santos, Raquel S.; Moraes, Lillian; Samary, Cynthia S.; Santos, Cíntia L.; Ramos, Maíra B. A.; Vasconcellos, Ana P.; Horta, Lucas F.; Morales, Marcelo M.; Capelozzi, Vera L.; Garcia, Cristiane S. N. B.; Marini, John J.; Gama de Abreu, Marcelo; et al.
Abstract : BACKGROUND: Large tidal volume (VT ) breaths or "recruitment maneuvers" (RMs) are used commonly to open collapsed lungs, but their effectiveness may depend on how the RM is delivered. We hypothesized that a stepped approach to RM delivery ("slow" RM) compared with a nonstepped ("fast" RM), when followed by decremental positive end-expiratory pressure (PEEP) titration to lowest dynamic elastance, would (1) yield a more homogeneous inflation of the lungs, thus reducing the PEEP obtained during post-RM titration; (2) produce less lung morphofunctional injury, regardless of the severity of sepsis-induced acute lung inflammation; and (3) result in less biological damage in severe, but not in moderate, acute lung inflammation. METHODS: Sepsis was induced by cecal ligation and puncture surgery in 51 Wistar rats. After 48 hours, animals were anesthetized, mechanically ventilated (VT = 6 mL/kg), and stratified by PO2 /fraction of inspired oxygen ratio into moderate (≥300) and severe (<300) acute lung inflammation groups. Each group was then subdivided randomly into 3 subgroups: (1) nonrecruited; (2) RM with continuous positive airway pressure (30 cm H2 O for 30 seconds; CPAPRM or fast RM); and (3) RM with stepwise airway pressure increase (5 cm H2 O/step, 8.5 seconds/step, 6 steps, 51 seconds; STEPRM or slow RM), with a maximum pressure hold for 10 seconds. All animals underwent decremental PEEP titration to determine the level of PEEP required to optimize dynamic compliance after RM and were then ventilated for 60 minutes with VT = 6 mL/kg, respiratory rate = 80 bpm, fraction of inspired oxygen = 0.4, and the newly adjusted PEEP for each animal. Respiratory mechanics, hemodynamics, and arterial blood gases were measured before and at the end of 60-minute mechanical ventilation. Lung histology and biological markers of inflammation and damage inflicted to endothelial cells were evaluated at the end of the 60-minute mechanical ventilation. RESULTS: Respiratory system mean airway pressure was lower in STEPRM than that in CPAPRM . The total RM time was greater, and the RM rise angle was lower in STEPRM than that in CPAPRM . In both moderate and severe acute lung inflammation groups, STEPRM reduced total diffuse alveolar damage score compared with the score in nonrecruited rats. In moderate acute lung inflammation, STEPRM rats compared with CPAPRM rats had less endothelial cell damage and angiopoietin (Ang)-2 expression. In severe acute lung inflammation, STEPRM compared with CPAPRM reduced hyperinflation, endothelial cell damage, Ang-2, and intercellular adhesion molecule-1 expressions. RM rise angle correlated with Ang-2 expression. CONCLUSIONS: Compared with CPAPRM, STEPRM reduced biological markers associated with endothelial cell damage and ultrastructural endothelial cell injury in both moderate and severe sepsis-induced acute lung inflammation. Abstract : Supplemental Digital Content is available in the text.Published ahead of print February 1, 2016